(untitled) (American Journal of Management, 2025)
This study examines the environmental management practices of sugar mills in the Philippines, assessing current strategies in pollution control, waste management, and energy efficiency. Through surveys and focus group discussion, the research explores how selected mills implement green practices and adopt cleaner technologies. Results show varying levels of environmental commitment, with some mills demonstrating innovation in waste management and resource conservation. The study identifies challenges in policy support and technological access, offering a framework to enhance sustainability across the industry. These findings contribute to ongoing efforts to green the sugar industry and promote ecological modernization in agro-industrial sectors.